A comparative analysis of the evolution of the business internationalization process: The Western Balkans and the EU member states in CEE - Dumitru-Silviu Mistreanu (CES Working Papers, 2023)
The term internationalization has been mainly used to show the expansion of economic activities of firms outside of their home country where they aim at capturing a bigger market. The Central and Eastern Europe region has gone through a process of market transition over the past few decades, yet the business internationalization process has played an important role in the states' economies. The aim of this paper is to analyze the firm internationalization process in the new member states and the Western Balkans countries and gain a better understanding of the process and its course over time. Due to different geopolitical circumstances, the Western Balkan countries did not attract as many investors as much as the EU member states in CEE did that have had a constant flow of investments once they were members of the EU.
Keywords: 330; internationalization; foreign trade; evolution; business; CEE; EU; Western Balkans